HOW SHOULD WE SUPPORT PATIENTS WITH PRIMARY BRAIN TUMOURS WHO ELECT TO TAKE CANNABINOIDS?. (3rd October 2018) - La, Jessica; Hurwitz, Victoria; Mullens, Laura; Brazil, Lucy; Gullan, Richard; Bhangoo, Ranj; Vergani, Francesco; Beaney, Ronald; Ashkan, Keyoumars; Rooprai, Bali; Swampillai, Angela
Abstract: INTRODUCTION: Primary brain tumours account for 3% of new cancer cases (2015) but account disproportionately in terms of mortality and morbidity. With radical treatment prognosis is variable; ranging from 80% survival for 5 years or more for benign meningiomas to a dismal 5% for Glioblastoma multiforme (GBM). Understandably, increasing numbers of cancer patients are seeking Complementary and Alternative Medicine (CAM) to improve prognosis and alleviate treatment related toxicities. There is legitimate CAM research in the UK. Yet it is challenging for vulnerable patients to disentangle legitimate researchers from dubious ones. These patients are open to manipulation and abuse via unsolicited sources offering a magical 'cure'. It is also challenging to support patients through treatment when they may be self-medicating without their treating team being aware of the details, and possible interactions. We propose to investigate whether there is a need for specialist support for this patient population. METHOD: Questionnaires were distributed across 3 Neuro oncology clinics over one week (N=51). These were completed anonymously to encourage honest responses. 30 patients were on active surveillance and 21 patients were on active treatment (either radiotherapy or chemotherapy). RESULTS: A significant number of patients were already taking some form of CAM such as turmeric, or were interested in speaking to a CAM Specialist regarding it. Of particular interest was the use of Cannabinoids (CBD) which are being explored in pre-clinical and clinical trials in brain tumours. CONCLUSION: We are seeing an increase in the use of CBD use amongst our patient groups who were surveyed. This survey has given us insight into our patient population and guides us on how we can best support them. We are continuing to collect questionnaires and full evaluation will be presented.